Inseminação artificial versus monta natural em bovinos de corte: aspectos reprodutivos, produtivos e econômicos - Paulo Eduardo Machado Goncalves (2008)
The objective of this study was to evaluate pregnancy rates in two beef cattle production systems (natural mating and artificial insemination), the performance of progenies and its interrelated economic factors. I was used 205 days adjusted weaning weight, pregnancy rates and economic factors from a property located in Mato Grosso, from 2002 to 2006. When compared the pregnancy rates, for years 2002, 2003 and 2004, from inseminated mature cows (88.2%, 86.4%, 81.5%) with natural matings (90.2%, 87.2%, 87.0%), no differences (p> 0.05) between the two groups were registered. However in 2003, for primiparous cows, lower pregnancy rates in the artificial inseminated group (49.0%) was observed when compared to natural mating group (76.6%) p<0.05. I was registered higher 205 days weaning weight and average daily gain in calves from inseminated cows in relation to those from natural matings (p <0.05). No correlation (p>0.05) between 205 days weight or average daily gain and expected differences progenies, we observed in the group of inseminated animals. Pregnancy cost was estimated in US$8.00* for the inseminated group, corresponding to 2.23 times the estimated cost in the natural mating group. Both systems were profitable, with the AI surpassing by 4.78% the natural mating, probably due to the small number of experimental animals, mainly in the natural mating group, not allowing dilution of fixed costs.